Na politicheskom Olimpe . Na politicheskom Olimpe . On the Political Olympus . На политическом Олимпе - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing resigned politicians. Featured in the program: IAvlinskii, Grigorii Alekseevich (Deputy of the State Duma); Pamfilova, Ella Aleksandrovna (Politician) Contributors: Kurkova, Bella Alekseevna (Anchor) Передача рассказывает об отставных политиках. В программе участвуют: Явлинский, Григорий Алексеевич (Депутат Государственной Думы); Памфилова, Элла Александровна (Политик) Создатели: Куркова, Бэлла Алексеевна (Ведущий/Ведущая)